2021
DOI: 10.1093/icvts/ivab046
|View full text |Cite
|
Sign up to set email alerts
|

Reverse remodelling after aortic valve replacement for chronic aortic regurgitation

Abstract: OBJECTIVES This study aimed to assess the long-term outcomes and investigate the factors related to left ventricular (LV) reverse remodelling after aortic valve replacement (AVR) in patients with chronic aortic regurgitation (AR). METHODS A total of 246 patients who underwent AVR for chronic AR at our institution were included in this retrospective study. Primary end-points included all-cause mortality, cardiac mortality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…62 In the general population, RR after surgical aortic valve surgery for either stenosis or regurgitation is predicted by a higher preoperative LVEF and lower LVESV, while patients with severe LV dysfunction usually do not experience RR. [144][145][146] A variable degree of RR, affecting LV function, size and mass, has been reported also in patients undergoing transcatheter aortic valve replacement (TAVR), following afterload reduction. 147,148 Even patients with low-flow, low-gradient aortic stenosis may experience RR after TAVR, 63 reasonably until the left ventricle has not been irreversibly damaged by the longstanding elevation of LV afterload.…”
Section: Interventional Procedures and Devicesmentioning
confidence: 98%
See 1 more Smart Citation
“…62 In the general population, RR after surgical aortic valve surgery for either stenosis or regurgitation is predicted by a higher preoperative LVEF and lower LVESV, while patients with severe LV dysfunction usually do not experience RR. [144][145][146] A variable degree of RR, affecting LV function, size and mass, has been reported also in patients undergoing transcatheter aortic valve replacement (TAVR), following afterload reduction. 147,148 Even patients with low-flow, low-gradient aortic stenosis may experience RR after TAVR, 63 reasonably until the left ventricle has not been irreversibly damaged by the longstanding elevation of LV afterload.…”
Section: Interventional Procedures and Devicesmentioning
confidence: 98%
“…In the general population, RR after surgical aortic valve surgery for either stenosis or regurgitation is predicted by a higher preoperative LVEF and lower LVESV, while patients with severe LV dysfunction usually do not experience RR 144–146 . A variable degree of RR, affecting LV function, size and mass, has been reported also in patients undergoing transcatheter aortic valve replacement (TAVR), following afterload reduction 147,148 .…”
Section: Heart Failure Treatment and Reverse Remodellingmentioning
confidence: 99%
“…For instance, Koga-Ikuta et al 13 showed that preoperative LVEF and LVESDi were significant predictors of LV reverse remodeling at 1 year after AVR, identifying an LVEF >49% and an LVESDi ≤33.2 mm/m 2 as optimal cut-off values. 13 In addition, Zhang et al 14 found that preoperative LVEF < 52% was a predictor of poor postoperative LV reverse remodeling. 14 Ideally, in a patient at an advanced age or with limited life expectancy and/or no more than moderate LV dilatation, concomitant MVA at the time of AVR could be avoided, also considering the increasing availability of percutaneous technology.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been published focusing on predictors of LV reverse remodeling following isolated AVR for isolated AR. For instance, Koga‐Ikuta et al 13 showed that preoperative LVEF and LVESDi were significant predictors of LV reverse remodeling at 1 year after AVR, identifying an LVEF >49% and an LVESDi ≤33.2 mm/m 2 as optimal cut‐off values 13 . In addition, Zhang et al 14 found that preoperative LVEF < 52% was a predictor of poor postoperative LV reverse remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic regurgitation (AR) is a common valvular pathology affecting up to 15% of the population, of which 1.6% have moderate to severe AR 1 . It a progressive disease of both the valve and myocardium with worsening regurgitation associated with adverse cardiac remodeling and function‐ left ventricular hypertrophy and dilatation followed by diastolic and systolic dysfunction 2,3 . Patients present with dyspnoea and less often with angina 3–5 .…”
Section: Introductionmentioning
confidence: 99%